2019
DOI: 10.1107/s2053229619002225
|View full text |Cite
|
Sign up to set email alerts
|

A survey of interactions in crystal structures of pyrazine-based compounds

Abstract: The important role of pyrazine (pz) and its derivatives in fields such as biochemistry and pharmacology, as well as in the study of magnetic properties, is surveyed. Recognition of these properties without extensive investigations into their structural properties is not possible. This review summarizes interactions that exist between these organic compounds by themselves in the solid state, as well as those in coordination polymers with metal ions and in polyoxometalatebased hybrids. Complexes based on pyrazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 136 publications
0
14
0
Order By: Relevance
“…These ligands feature the N,N 0 ,O-coordination mode via one of the pyrazine N, the imine N and the iminol O atoms. In general, pyrazine derivatives have been found to have great importance in biochemistry courtesy of their chemical functionality (Kenwood et al, 2015;Koleša-Dobravc et al, 2017;Taghipour & Mirzaei, 2019). In our previous report, we revealed that mononuclear Cu II complexes based on pyrazine-acylhydrazone ligands showed strong activity against jack bean urease (Qin et al, 2016).…”
Section: Introductionmentioning
confidence: 91%
“…These ligands feature the N,N 0 ,O-coordination mode via one of the pyrazine N, the imine N and the iminol O atoms. In general, pyrazine derivatives have been found to have great importance in biochemistry courtesy of their chemical functionality (Kenwood et al, 2015;Koleša-Dobravc et al, 2017;Taghipour & Mirzaei, 2019). In our previous report, we revealed that mononuclear Cu II complexes based on pyrazine-acylhydrazone ligands showed strong activity against jack bean urease (Qin et al, 2016).…”
Section: Introductionmentioning
confidence: 91%
“…Like many reports where intermolecular interactions are investigated on the basis of geometrical considerations (Le et al, 2015;Galek et al, 2014;Vahdani Alviri et al, 2020;Sabbaghi et al, 2021;Bojarska et al, 2020;Taghipour & Mirzaei, 2019), the CSD was used via ConQuest software (Version 5.42 of November 2020; Groom et al, 2016). For 1 and 2, the occurrence percentages of a synthon in both crystals were determined together with the number of hits having this synthon and the number of hits having the considered moieties.…”
Section: Cambridge Structural Database (Csd) Analysismentioning
confidence: 99%
“…One of the promising approaches toward the synthesis of this kind of material is combining metal-substituted POMs with organic or metal–organic fragments to make inorganic–organic hybrid-based LPOMs. Various POM-based inorganic–organic hybrids with interesting structural and functional properties were reported [ 23 , 24 , 25 ]. In this field, a certified fact is that the synthesis of such hybrids depends on the selection of POMs as inorganic building blocks and organic ligands as structure-directing and functional components.…”
Section: Introductionmentioning
confidence: 99%